An investigation using the choice experiment method into options for reducing illegal bushmeat hunting in western Serengeti. Issue 1 (12th September 2012) - Moro, Mirko; Fischer, Anke; Czajkowski, Mikołaj; Brennan, Dervla; Lowassa, Asanterabi; Naiman, Loiruck C.; Hanley, Nick
Abstract Bushmeat hunting is perceived as a serious threat to the conservation status of many species in Africa. We use a novel livelihood choice experiment method to investigate the role of illegal hunting within livelihood strategies in the western Serengeti, and to identify potential trade‐offs between illegal hunting and other income sources. We find that increasing access to microcredit, higher wages, increases in number of cows, weeks hunting and increased access to market all contribute to well‐being. We are able to quantify the trade‐offs between weeks spent illegal hunting and increases in cattle, wage income, access to markets, and access to microcredit. However, important differences emerge in response to these variables between different wealth groups which shape how we should design conservation and development interventions.